2022
DOI: 10.3389/fcell.2022.1007641
|View full text |Cite
|
Sign up to set email alerts
|

Pathological implications of metabolic reprogramming and its therapeutic potential in medulloblastoma

Abstract: Tumor-specific alterations in metabolism have been recognized to sustain the production of ATP and macromolecules needed for cell growth, division and survival in many cancer types. However, metabolic heterogeneity poses a challenge for the establishment of effective anticancer therapies that exploit metabolic vulnerabilities. Medulloblastoma (MB) is one of the most heterogeneous malignant pediatric brain tumors, divided into four molecular subgroups (Wingless, Sonic Hedgehog, Group 3 and Group 4). Recent prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 167 publications
1
4
0
Order By: Relevance
“…Our findings demonstrate that MP1 not only inhibits MYC protein expression in MB, but also key pathways under its transcriptional control, such as cell cycle, protein synthesis/translation and metabolic pathways. Importantly, we and others have previously shown that mTOR/translation and metabolic pathways are highly activated in MYC-driven MB [ 23 , 37 ], which is consistent with MP1 having anticancer mechanism(s) that target these cellular pathways downstream of MYC. Together, these data suggest that MYC is the key target for MP1.…”
Section: Discussionsupporting
confidence: 82%
“…Our findings demonstrate that MP1 not only inhibits MYC protein expression in MB, but also key pathways under its transcriptional control, such as cell cycle, protein synthesis/translation and metabolic pathways. Importantly, we and others have previously shown that mTOR/translation and metabolic pathways are highly activated in MYC-driven MB [ 23 , 37 ], which is consistent with MP1 having anticancer mechanism(s) that target these cellular pathways downstream of MYC. Together, these data suggest that MYC is the key target for MP1.…”
Section: Discussionsupporting
confidence: 82%
“…Although MYC is associated with a glycolytic phenotype [ 10 , 43 45 ], stimulation of aerobic ATP production and anabolic pathways for biomass generation under normoxic conditions has been described [ 11 ]. In accordance, a recent review outlining metabolic characteristics of MB established thus far concluded that aerobic glycolysis and OXPHOS might be coexistent in MB [ 40 ]. Furthermore, the electron transport chain is closely linked to the metabolism of nucleotides [ 18 ].…”
Section: Discussionmentioning
confidence: 54%
“…Many factors influence cell metabolism, leading to diverse metabolic phenotypes even within one tumour entity [ 11 ]. While there have been other studies analysing metabolism in MB, we are only beginning to understand metabolic heterogeneity between MB groups [ 40 ]. Park et al, for example, established prognostically relevant metabolic pathways for SHH, G3 and G4 MB by exploring RNA expression data of the MAGIC cohort [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tissue analysis of metabolites showed that MBs have higher lipid levels compared to other atypical teratoid/rhabdoid tumors [ 172 ]. It has been shown that MYCN could be a downstream target of the shh pathway in MB and its role in the regulation of glycolytic metabolism was studied in MB models [ 166 , 173 ]. However, the role of MYCN in the regulation of lipid metabolism still needs to be explored.…”
Section: Lipid Metabolism In Embryonal Tumorsmentioning
confidence: 99%